Effect of plant-derived exosome-like nanoparticles in ultraviolet-induced skin photoaging - Dong, Hai; Deng, Yi; Li, Jiayan; Lin, Wen; Luo, Yangyan; Jiang, Yuan (Frontiers in Pharmacology, 2025)
Long-term exposure to ultraviolet (UV) irradiation leads to skin photoaging. The mechanism of photoaging is complex, involving oxidative stress, inflammation, and collagen degradation. Certain active ingredients derived from plants possess strong antioxidant and anti-inflammatory properties and have been utilized in cosmeceuticals for cosmetic medicine. Plant-derived exosome-like nanovesicles (PELNs) contain bioactive constituents obtained from plant cells, which contribute to PELNs possessing multiple pharmacological functions, making them beneficial to skin care. Some researchers used PELNs as natural agents to attenuate UVB-induced skin photoaging, and their findings are critical for discovering novel anti-photoaging treatment modalities. In this mini-review, we focus on the related research of PELNs and UVB-induced skin photoaging, and introduce the protective role of PELNs. Finally, we will discuss the challenges and future directions in the development of PELNs for anti-photoaging.